Active drag related to body dimension - Huijing, P. A.; Toussaint, H. M.; Mackay, R. (Swimming Science V, 1988)
During this century, a great deal of attention has been given to the presupposed relationship between body shape and dimensions and hydrodynamic resistance (Alley, 1949; Amar, 1920; Clarys, 1976, 1979; Oarys, Jiskoot, Rijken, & Brouwer, 1974; Counsilman, 1951; Gadd, 1963; Jaeger, 1937; Jurina, 1972, 1974; Karpovich, 1933; Klein, 1939; Liljestrand & Stensstrom, 1919; Lopin, 1947; Miyashita & Tsunoda, 1978; Onoprienko, 1967; Safarian, 1968; Schramm, 1960, 1961; Tews, 1941; Tilborg, Daly, & Persijn, 1983; Zaciorski & Safarian, 1972). However, only Oarys (1976, 1979) related drag for actively swimming subjects (active drag) to anthropometric variables. Contrary to expectations, Oarys (1976, 1979) found only few correlations between active drag and anthropometric variables, which forced him to conclude that the shape of the human body has hardly any influence on active drag and that other factors are therefore more important. Given the fact that some argue that drag force is directly proportional to the product of velocity squared and a constant of proportionality, which among other things is dependent on the (projected) area of the body exposed to flow (Rouse, 1946), one would expect at least some relationship between this variable and drag. The development of a new method of determining active drag (MAD system) (Hollander et al., 1986) warranted a reevaluation of this relationship, which was the aim of the present work.